Analisis Strategi Peningkatan Mutu Pendidikan Islam Di Era Digital - Gina Intana Dewi (Majalah Ekonomi, 2025)
This study examines strategic efforts to enhance the quality of Islamic education in the digital era. Digital advancements have significantly influenced various aspects of human life, including education. Islamic education, as a system that emphasizes the balance between worldly knowledge and spiritual values, is not immune to these technological shifts. To remain relevant and competitive in the global educational landscape, it is essential to improve the quality and adaptability of Islamic education. This research adopts a qualitative method through a literature review approach. Data were collected from books, peer-reviewed journals, and previous research related to Islamic education and digital transformation. The research process involved four main stages: preparing research tools, compiling a bibliography, organizing a schedule, and conducting systematic reading and note-taking. The collected data were critically analyzed to build strong theoretical foundations and support the formulation of strategic recommendations. The results indicate that enhancing Islamic education in the digital age requires several key strategies: strengthening accreditation standards, integrating technology into the learning process, and maximizing the use of digital platforms. Additionally, teacher empowerment through continuous training, building partnerships with relevant stakeholders, and promoting active community involvement in value-based education are essential. This study highlights the need for continuous innovation and reform to ensure that Islamic education produces a generation that is not only technologically literate but also morally and spiritually grounded